Food Price Volatility and Agricultural Welfare in Emerging Economies: Evidence from Provincial Indonesia - Setiadi; Sumastuti, Efriyani; Rakhmawaty, Yunissa (Moneta : Journal of Economics and Finance, 2024)
Food price volatility has emerged as one of the most pressing challenges for emerging economies, with Indonesia representing a critical case where agriculture sustains rural livelihoods and food accounts for more than 50% of household spending. This study addresses a gap in the literature by examining how food inflation and its volatility shape the agricultural terms of trade (NTP) across 34 provinces from 2017 to 2023. The research employs a mixed method econometric design, combining Vector Error Correction Models (VECM) and Two Stage GARCH models. VECM is used to explore both short run and long run relationships between inflation components and NTP, while GARCH captures the volatility effects of food prices and macroeconomic shocks, including exchange rate fluctuations and climate anomalies. Data were collected monthly from official Indonesian statistical sources, including BPS, Bank Indonesia, and BMKG. Results reveal that food inflation significantly influences NTP in both the short and long run, while core inflation remains statistically insignificant. Although farmers may initially gain from rising food prices, these gains are offset in the long term by rising input costs and supply chain constraints. The GARCH analysis confirms that volatility in food inflation undermines farmer welfare, with heterogeneous effects across provinces depending on agricultural structure and resilience to shocks. These findings highlight the limitations of Indonesia’s Inflation Targeting Framework (ITF) in addressing food price volatility and call for more inclusive policy strategies. Non-monetary interventions such as strategic food reserves, subsidies, and food distribution programs are recommended, alongside stronger coordination between monetary and agricultural institutions. Case studies from Brazil and Ghana further support integrated approaches that combine food security with macroeconomic planning. The study contributes to the literature by offering empirical insights into how inflation volatility affects agricultural welfare in an emerging economy. It advocates for a multi-dimensional policy framework to ensure rural resilience, equitable economic development, and food system stability in the face of growing macroeconomic uncertainties.